2018
DOI: 10.1080/10934529.2018.1438821
|View full text |Cite
|
Sign up to set email alerts
|

Model based evaluation of plant improvement at a large wastewater treatment plant (WWTP)

Abstract: In this work, the effect of the improvement carried out at a large-scale wastewater treatment plant (WWTP) was evaluated, by means of modelling works, with the aim to determine the influence of the modernization over the process performance. After modernization, the energy consumption due to the aeration decreased about a 20% maintaining the effluent quality. In order to double-check the good effluent quality, modelling works were carried out at the full-scale plant. After calibration, the model was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…For a "Klimzowiec" WWTP a period of intensive monitoring and sampling probes, which was more than 6 months in duration. Data sets from the full-scale plant (including tracer test and the laboratory/online measurements) were used from this study (as was presented in Table 2 and 3) and compared with historical data and a previous study [2,15]. All these investigations were further used for steady-state and then dynamic-state simulations in the WEST software to accurately calibrate the studied WWTP model.…”
Section: Integration Of Previsys Advanced Supervisory Control System mentioning
confidence: 99%
See 2 more Smart Citations
“…For a "Klimzowiec" WWTP a period of intensive monitoring and sampling probes, which was more than 6 months in duration. Data sets from the full-scale plant (including tracer test and the laboratory/online measurements) were used from this study (as was presented in Table 2 and 3) and compared with historical data and a previous study [2,15]. All these investigations were further used for steady-state and then dynamic-state simulations in the WEST software to accurately calibrate the studied WWTP model.…”
Section: Integration Of Previsys Advanced Supervisory Control System mentioning
confidence: 99%
“…By using advanced software (WEST, GPS-x, SIMBA, AQUASIM, etc. ), it is possible to create a model of a full-scale WWTP in order to run a simulation and, subsequently, interpret results under various operational conditions [1][2][3]. The laboratory tests, online measurements and additional calculations (e.g., COD fractions and biochemical processes rates) should be carried out to better integrate the computer model to the conditions prevailing in the local parameters of each individual part of WWTPs [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amount of ammonia in treated water from the MWWTP based on TF/AS process and the MWWTP based on NTF/AS process were 1.38 and 1.29 mg/dm 3 , respectively; which were lower than standard value of about 2 mg/dm 3 (the maximum concentration of ammonia and ammonia compounds allowed for the fish at a temperature of 18 °C and pH of 5-7) [1, 12]. Drewnowski et al [25] studied the effect of the improvement performed at a large-scale WWTP by means of modeling works and reported the rate of the main processes depending on the aeration, that is oxygen uptake rate (OUR) and ammonia uptake rate (AUR), to be about 22 g O 2 /(kg VSS·h) and 2.9 g N/(kg VSS·h), respectively [25].…”
Section: Performance Of the Mwwtps Based On Tf/as And Ntf/as Processesmentioning
confidence: 99%
“…Drewnowski et al [25] evaluated the effect of the improvement performed at a large-scale WWTP by means of modeling works, with the aim to determine the influence of the modernization over the process performance. They concluded that the energy consumption because of the aeration reduced about a 20 % maintaining the effluent quality [25].…”
Section: Introductionmentioning
confidence: 99%